Quality of life and cognitive functions in early onset multiple sclerosis. (January 2016) - Lanzillo, R.; Chiodi, A.; Carotenuto, A.; Magri, V.; Napolitano, A.; Liuzzi, R.; Costabile, T.; Rainone, N.; Freda, M.F.; Valerio, P.; Brescia Morra, V.
Abstract: Background: Multiple sclerosis (MS) is a demyelinating disease of the CNS occurring in young adults and even in children in 5% of cases. Lower quality of life (QoL) and cognitive impairment (CI) (40–54%) have been reported in early-onset MS (EO-MS) patients. Objective: To assess QoL and cognitive function in EO-MS and their relationship, also considering demographic and clinical variables. Methods: Paediatric Quality of life inventory Version 4.0 for patients aged 13–18 and 19–25 years, Beck Depression Inventory II (BDI II) and the Rao Brief Repeatable Battery were performed in EO-MS patients (onset age ≤25years). EDSS and MSSS were performed at same time. After testing for normal distribution, group comparisons were performed through the two-tailed Student's t test, one-way analysis of variance (ANOVA) and linear or logistic regression when appropriate. The Bonferroni correction for multiple testing was used when appropriate. Results: 59 patients were included (mean age: 20 ± 3.6; Female sex 52.54%). 34 patients had a paediatric onset (<18 years) while 20 patients had a juvenile onset (18 < age < 25 years) of disease. 5 patients were excluded for missing data. HR-QoL was higher in paediatric than juvenile MS patients (p = 0.02), and it was inversely related to EDSS (p = 0.0005) and Multiple Sclerosis Severity score (MSSS) (p = 0.0001). Sixtyone % of patients showed a CI at BRB. No association was found between CI and any socio-demographic and clinical data. HR-QoL total score was not related to CI status nor to any domain-specific cognitive function score, even considering BDI as possible bias. CI was related to social, physical functioning score and EDSS (p = 0.01) at a logistic regression backward stepwise estimation. Conclusion: HR-QoL resulted to be better in paediatric than juvenile MS onset patients and was inversely related to rapidity of disability accumulation, while cognitive impairment was influenced by physical disability and poor social involvement (school, education …). Social participation, affective relations and psychological flexibility could have a protective function on CI. Highlights: HR-QoL was higher in paediatric onset (<18 y) than juvenile onset (18 < x < 25) MS patients (p = 0.02). HR-QoL was inversely related to EDSS (p = 0.0005) and multiple sclerosis severity score (MSSS) (p = 0.0001). QoL was not related to disease duration, but to rapidity of disability accumulation.